Teaching vocabulary to 8th graders in the Cuenca Beauty Academy - SanMartín C., Daniela; Sumba M., Lourdez
Through this research, we noticed the Constructivist Theory, which encourages students to use active techniques to create more knowledge and to reflect on what they are doing. Also, we took into account Vygotsky´s theory, which points that since children are born into a social world, learning occurs through interaction with other people. These theories supported us to reflect about vocabulary importance and its acquisition, and also to implement teaching techniques to present, practice, and help students comprehend the target words and use them. In addition, we considered a number of techniques that facilitate teachers to present new vocabulary items, which are classified according to visual and verbal techniques. Among the visual aids we have flashcards, pictures, drawings, realia, mime and actions, and others. Verbal techniques consist of using illustrative sentences, descriptions, synonyms and antonyms, scales, word sets, sounds, and verbal definitions. On the other hand, motivation has a great effect on a student´s capacity to learn; therefore, learners need to be involved in making decisions over what they are doing. For that reason, we selected some activities which include word hunt, word association, word dominoes, and games, such as memory, guessing, find the differences, crosswords and board games that teachers can use in the classroom while teaching vocabulary. Finally, since the ultimate goal of learning a language is communicative competence, and a beneficial relationship between teacher and students and their interaction is important, the application of these activities and games will be useful to achieve those objectives